Inequalities in children's exposure to alcohol outlets in Scotland: a GPS study - Fiona M. Caryl; Jamie Pearce; Rich Mitchell; Niamh K. Shortt (BMC, 2022)
Abstract Background Alcohol use is a leading cause of harm in young people and increases the risk of alcohol dependence in adulthood. Alcohol use is also a key driver of rising health inequalities. Quantifying inequalities in exposure to alcohol outlets within the activity spaces of pre-adolescent children-a vulnerable, formative development stage-may help understand alcohol use in later life. Methods GPS data were collected from a nationally representative sample of 10-and-11-year-old children (n = 688, 55% female). The proportion of children, and the proportion of each child's GPS, exposed to alcohol outlets was compared across area-level income-deprivation quintiles, along with the relative proportion of exposure occurring within 500 m of each child's home and school. Results Off-sales alcohol outlets accounted for 47% of children's exposure, which was higher than expected given their availability (31% of alcohol outlets). The proportion of children exposed to alcohol outlets did not differ by area deprivation. However, the proportion of time children were exposed showed stark inequalities. Children living in the most deprived areas were almost five times more likely to be exposed to off-sales alcohol outlets than children in the least deprived areas (OR 4.83, 3.04-7.66; P < 0.001), and almost three times more likely to be exposed to on-sales alcohol outlets (OR 2.86, 1.11-7.43; P = 0.03). Children in deprived areas experienced 31% of their exposure to off-sales outlets within 500 m of their homes compared to 7% for children from less deprived areas. Children from all areas received 22-32% of their exposure within 500 m of schools, but the proportion of this from off-sales outlets increased with area deprivation. Conclusions Children have little control over what they are exposed to, so policies that reduce inequities in alcohol availability should be prioritised to ensure that all children have the opportunity to lead healthy lives.